defense cooperation policy, benefits, implications, military preparedness Policy Effectiveness: Indonesia-China Defense Cooperation Study - Agus Purwo Wicaksono (Journal Of Social Science (JoSS), 2022)
Each country carries out defense cooperation with different levels of commitment. This study aims to analyze the factors that influence KPIT in increasing the readiness of the Indonesian military. As a follow-up, the Indonesian government, in this case the Ministry of Defense, has implemented regulatory and allocative actions. Several rules have been published, socialized, controlled and supervised. The appointment of officials has been carried out and supported by existing resources, so that all activities according to the agreement of the two countries have been carried out. Defense cooperation is hypothesized to be useful and has implications for military preparedness even though it is influenced by the strategic environment. Primary data was collected through a survey of 95 people who had participated in KPIT activities, interviews and focus group discussions with competent parties. Secondary data obtained from various documents. The collected data were analyzed using a qualitative approach supported by quantitative data. The results of the analysis show that KPIT activities have very little impact on military preparedness in Indonesia. However, these activities are very beneficial for the actors and have huge implications for individual alertness. This study also found that KPIT activities contributed to increasing Indonesia's national strength through military preparedness. Exchange of information and the defense industry can improve the quality of organization, doctrine, policies, military education curricula, transfer of defense equipment technology, including the possibility of joint production. Joint military exercises can improve anti-terror capabilities, military self-defence, hostage release, and others.